A correlation between the Large Igneous Provinces and mass extinctions: constraint on the end-Guadalupian mass extinction and the Emeishan LIP in South China, eastern Tethys. Issue 10 (26th July 2016) - Tian, Xuesong; Shi, Zejin; Yin, Guan; Long, Hongyu; Wang, Kun
ABSTRACT: Well-documented outcrops around the Emeishan Large Igneous Province (ELIP) in South China, eastern Tethys, encompassing the end-Guadalupian mass extinction have been investigated. Correlatable sections recording the event exhibit very similar lithological characters, positive-then-negative C isotope excursions and massive biotic demise. Detailed analyses of the fossil record and carbon isotopic variations were carried out on the Guadalupian–Wuchiapingian Boundary sections over the inner, middle, outer zones of the ELIP and its margin. Due to a pronounced decrease in marine habitat area and the environmental and ecological change over this part of the Tethys, the biota crisis records show the loss of numerous tropical invertebrate taxa, and exhibit fewer genera and smaller testing sizes and low productivity. The biota crisis was a sustainable and gradual reduction in diversity over the Capitanian. The associated carbon isotopic data reveal unusually high δ 13 C(carb) values before the late Capitanian, representing higher primary productivity (or buried rate) and more 13 C-enriched CO2 released by hydrothermal carbonate breakdown from the upper crust into the sediments at that time. Subsequently, an accelerated negative excursion across the boundary and the gradual excursion with low carbon isotope amplitude favours an increased influx of light 12 C sourced by the volcanism around the eastern Tethys. The very similar time–space relation between the biota crisis and the Emeishan volcanism confirms that volcanic eruptions may have triggered the biota crisis event in South China. Intensive volcanism could result in detrimental environmental and ecological stresses, habitat loss, organic material splitting, or the emission of light carbon and thermal fluid (or aerosol), implying that the losses of the shallow-marine invertebrates either occurred geologically instantaneously or in a series of closely spaced crises coinciding with the initial phase of ELIP formation. These findings in South China may reveal the causal relation between mass extinctions and LIPs in a global context.